Pelatihan Trouble Shooting Sistem RO di Kecamatan Marusu Kabupaten Maros - Dewiani Dewi Djamaluddin; Muh Anshar; Zaenab Muslimin; Elyas Palantei; Merna Baharuddin; Andini Dani Achmad; Wardi -; Syafruddin Syarif; Rhiza S. Sadjat (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2019)
This past year in Tellumpoccoe Village has made effective the performance of equipment with hybrid water supply technology through pump wells and automation technology and integrated filtering systems to improve water quality. For household level consumption, a family sample is taken to clean water and provide assistance during the installation process and the feasibility test for filtered water consumption. Besides that, an engineering team of 26 people had formed. With the passage of time the equipment has been able to be used by the community in tellumpoccoe village well until a major flood disaster occurred in early October last year 2018. So that as a result of the flooding the RO equipment was soaked so that it could no longer be used. New problems arise because of the ignorance of the community to improve the tool. So as to overcome these problems, training is conducted to overcome the existing problems so that the equipment can be reused. So that this community service activity was held which aims to provide training on how to maintain and repair (Trouble Shooting) the existing RO system so that villagers will be able to maintain the sustainability of the clean water mechanism.